Wind pressure coefficients for roof ventilation purposes. Issue 175 (April 2018) - Gullbrekken, Lars; Uvsløkk, Sivert; Kvande, Tore; Pettersson, Kaj; Time, Berit
Abstract: Wind pressure coefficients (cp ) are important inputs for analytical calculations of wind load. The aim of this research is to investigate wind pressure coefficients on a test house located in Norway in order to pave the way for improved analysis of wind-driven roofing ventilation. The large-scale test measurements show that the wind pressure coefficient along the eaves of the house varies with different wind approach angles. Assuming wind-driven air flow through the air cavity beneath the roofing, an average Δ c p ¯ value of 0.7 is derived for practical engineering purposes. The results from the study are applicable for single or two-storey houses with pitched roofs at different roof angles. Highlights: Full-scale measurements of wind pressure coefficients of a routable test house is presented. The wind pressure coefficients of the facade varies with different wind approach angles. The distribution and values of the wind pressure coefficient are in line with previous field and laboratory investigations. A Δ c p ¯ of 0.7, needed for engineering evaluations, was calculated. The results from the study are applicable for one to two storey buildings with pitched roof and different roof angles.